Zaufanie młodzieży licealnej do instytucji = Confidence of secondary school students in institutions - Papiór, Elżbieta; Roszkowska, Martyna (Zielona Góra: Lubuskie Towarzystwo Naukowe)
Sociological literature expresses views that the key to efficient democracy lies in building social capital. Social trust is an essential constituent of social capital, in particular trust in political parties and political institutions associated with the executive (government, police, military), the legislative (parliament), and the judiciary (prosecutor`s office, courts, constitutional tribunal) branch. According to many researchers, trust put in these institutions plays a major role in the development of beliefs and attitudes towards democracy. The article presents views and assessments on the functioning of social institutions in Poland given by secondary school graduates from Zielona Gora.
Keywords: szkolnictwo ponadpodstawowe; młodzież szkolna; instytucje publiczne; zaufanie